IMPACT OF QUALITY OF WORK LIFE ON THE EMPLOYEE’S JOB SATISFACTION IN THE PRIVATE COLLEGES OF BANGALORE CITY - G, Muniraju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Teachers may not be able to show their dedication to effectively teaching the material and their talents may not be fully utilized if they are not satisfied with their current position. The study's primary goal is to investigate the variables influencing academic staff members' job satisfaction and work-life balance in private colleges of Bangalore City. To determine the outcomes for the hypothesis set, descriptive research approach was employed. Data was gathered through interviews and a structured questionnaire. All 75 private higher education institutions in Bangalore that provide management degrees were included in the sample frame. There were 172 lecturers in the sample. SPSS software is used for the analysis. To determine the link between the chosen variables, the regression equation tool was used for the investigation. The primary findings revealed that Promotion opportunity, Pleasurable work environment, Opportunity to share the idea, Respect for individual decisions, Participation in Mgt. Decision Making, Employees Unions, Employees Coordination, Proud to Work in an organisation, Career development, Reduced Frustration, Favourable legal policies, Self-Growth, Reputation of the organisation are the variables related to employees expected quality of work life have found significant with employee’s job satisfaction in private colleges of Bangalore city. Employees wellbeing, Employees equal consideration, No discrimination, Employees wellbeing, Employer Caring, Awards and rewards, Appropriate Vision and Mission, Performance appraisal, Respect for new ideas, Friendly Ownership, Liberal organisation policies, Best Employees awards etc, Work assignment based on capacity, Followed Government rules in HR, Adequate infrastructural and ICT facilities are the variables related to owner’s Characteristics have found significant with employee’s job satisfaction in private colleges of Bangalore city.